2022
DOI: 10.1111/aor.14442
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain is an early indicator of injury in ex vivo normothermic limb perfusion (EVNLP)

Abstract: Purpose There are no established criteria for discontinuing ex vivo normothermic limb perfusion (EVNLP) before irreversible damage occurs. This study evaluates weight gain as an indicator of injury during EVNLP. Methods Sixteen Yorkshire pig forelimbs were procured and preserved using EVNLP with a hemoglobin‐based oxygen carrier (HBOC‐201) or static cold storage. EVNLP continued until termination criteria were met: arterial pressure ≥ 115 mm Hg, compartment pressure > 30 mm Hg, or 20% reduction of oxygen satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Among the outcome metrics, weight gain and vascular resistance are the earliest and most critical parameters in organ machine perfusion. Meyers et al demonstrated that weight gain was correlated with microscopic muscle injury and was the earliest evidence of VCA dysfunction during ex - vivo normothermic limb perfusion in swine 34 . In addition, vascular resistance is closely linked to endothelial cell injury: shear-stress-induced injuries cause cellular edema, which eventually increases perfusion resistance by external compression of the microvessels 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the outcome metrics, weight gain and vascular resistance are the earliest and most critical parameters in organ machine perfusion. Meyers et al demonstrated that weight gain was correlated with microscopic muscle injury and was the earliest evidence of VCA dysfunction during ex - vivo normothermic limb perfusion in swine 34 . In addition, vascular resistance is closely linked to endothelial cell injury: shear-stress-induced injuries cause cellular edema, which eventually increases perfusion resistance by external compression of the microvessels 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the vascular resistance in the CS group was lower than in the CS + SNMP group. This highlights the ambivalence of SNMP, which, on one hand, allows for recovering the limb to a sub-physiological state while clearing toxic metabolites 22 and, on the other hand, exposes the graft to potential endothelial injuries 34 . More work is needed to balance the role of SNMP in supercooling techniques to reach optimized protocols, ensuring adequate recovery following extended preservation.…”
Section: Discussionmentioning
confidence: 99%
“…With a view to broadening future experimental applications, Kiermeir et al (2013) established a whole‐limb replantation model heterotopically replanting the limb 180° away from the axilla with a 7‐day endpoint. Comparisons between heterotopic replants and contralateral controls yielded no difference in compartment pressures and muscle morphology (despite reporting a 13% weight gain of replants, indicating skeletal muscle injury) (Meyers et al, 2022). Heterotopic limb transplant models do not allow assessment of bone healing and function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the EVNLP might provide a tool for assessing limb quality before transplantation. Our group has previously reported the implementation of EVNLP technology as a diagnostic tool for early limb dysfunction, elucidating the thresholds and parameters beyond which limb allografts are deemed suitable for transplantation or replantation (Meyers et al, 2022). Although the primary aim of this study was not to evaluate the application of EVNLP in limb transplantation, no vascular or infectious failures were encountered after short duration EVNLP.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis could be an increased toxic effect on the cells by EG, inducing cell lysis, while its lower viscosity limits turbulence and thereby endothelial damage induced edema. It has been suggested that weight gain is an early indicator of graft dysfunction in VCAs [ 31 , 32 ]. Therefore, the weight gain at the end of recovery should be of concern.…”
Section: Discussionmentioning
confidence: 99%